Security law and methods - Pastor, James F. (Butterworth-Heinemann, 2007)
Security Law and Methods examines suggested security methods designed to diminish or negate the consequence of crime and misconduct, and is an attempt to understand both the legal exposures related to crime and the security methods designed to prevent crime. The clear and concise writing of this groundbreaking work, as well as its insightful analysis of specific cases, explains crime prevention methods in light of legal and security principles.